“Smart Village” Digitization Program: Encouraging the Development of Village Potential in Juruan Daya, Sumenep - Angga Erlando; Rossanto Dwi Handoyo; Usma Nur Dian Rosyidah; Munir Munir; Andre Pupung Darmawan (Universitas Brawijaya, 2021)
Amid this modernization era, many areas in Indonesia still do not have good facilities and accessibility. This village is having difficulties, especially in the irrigation system, infrastructure, and accessibility to the internet. Hence, the authors proposed bringing Juruan Daya Village into a smart village digitalization program to overcome the problem. This program focuses on three significant aspects, such as (1) village administration and governance services; (2) village branding and its development and; (3) community empowerment through improving community business marketing management so that they can rely on more effective and efficient forms of digitalization. The method of this study used action research participatory and supported by secondary library research through journals, books, and other relevant resources. Then, after conducting training and pre-test and post-test to know the participants’ understanding of the program, the result shows that the residents are satisfied. They feel the benefits of the tower after attending the digitalization training in the aspects of village government services, village branding, and online marketing. Furthermore, there has been a development and improvement in participants' understanding of the implemented program. It is hoped that the villagers of Juruan Daya will be able to experience better community services in the future.